2015
DOI: 10.1093/reep/rev008
|View full text |Cite
|
Sign up to set email alerts
|

Global Warming and the Green Paradox: A Review of Adverse Effects of Climate Policies

Abstract: This article examines the possible adverse effects of well-intended climate policies. A weak Green Paradox arises if the announcement of a future carbon tax or a sufficiently fast rising carbon tax encourages fossil fuel owners to extract reserves more aggressively, thus exacerbating global warming.We argue that such policies may also encourage more fossil fuel to be locked in the crust of the earth, which can offset the adverse effects of the weak Green Paradox. We show that a subsidy on clean renewables has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…On the one hand, the negative welfare effect is stronger in case of a transition to the backstop technology, because of a "Green Paradox" effect (cf. Sinn, 2008;Van der Ploeg and Withagen, 2015): Along the path to the backstop technology, initial extraction is larger than along the path toward the fossil steady state, meaning 36 We have chosen units such that a unit of resource use results in a unit of carbon emissions. 37 We take a global output level of 75 trillion US$, corresponding with global output in 2013 (World Bank, 2014), and a carbon stock of 12,879 Gigaton, corresponding with the probable oil, natural gas, and coal reserves reported in Edenhofer and Kalkuhl (2009).…”
Section: Extension: Climatementioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the negative welfare effect is stronger in case of a transition to the backstop technology, because of a "Green Paradox" effect (cf. Sinn, 2008;Van der Ploeg and Withagen, 2015): Along the path to the backstop technology, initial extraction is larger than along the path toward the fossil steady state, meaning 36 We have chosen units such that a unit of resource use results in a unit of carbon emissions. 37 We take a global output level of 75 trillion US$, corresponding with global output in 2013 (World Bank, 2014), and a carbon stock of 12,879 Gigaton, corresponding with the probable oil, natural gas, and coal reserves reported in Edenhofer and Kalkuhl (2009).…”
Section: Extension: Climatementioning
confidence: 99%
“…As a result, the introduction of climate damages decreases welfare of the path leading to the backstop technology further than welfare of the path leading to the fossil steady state. On the other hand, the switch to the backstop technology reduces cumulative resource extraction, because part of the resource stock remains untapped, as in Van der Ploeg and Withagen (2014). If the marginal damage of carbon emissions is large enough, the social planner will even decide to leave the entire initial resource stock in situ and use the backstop technology from the beginning.…”
Section: Figure 11mentioning
confidence: 99%
“…It is well known from the Green Paradox literature (cf. Sinn, 2008Sinn, , 2012Van der Ploeg and Withagen, 2015) that climate policies such as subsidies on renewables or rapidly increasing carbon taxes may turn out to be counterproductive in a competitive but otherwise second-best world. When fossil fuels are traded competitively, upon the introduction of these climate policies owners of fossil fuel resources will supply more fossil fuel at the outset (Weak Green Paradox) and may extract faster over time so that also accumulation of carbon in the atmosphere is accelerated, and damages caused by climate change are increased (Strong Green Paradox).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we do not perform a welfare analysis of policy interventions (cf. Dasgupta and Heal, 1979;Van der Ploeg and Withagen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, whether the existence of catastrophic shifts implies a precautionary policy or not depends on the models' assumptions regarding risk-aversion, post-shift conditions and the imposed hazard-rate functions. In the climateeconomy context, van der Ploeg and de Zeeuw (2013) have shown that there are competing effects involved when considering the risk of climate-catastrophe events on optimal emission policy. In their model the existence of a potential tipping point also implies a "be-prepared" effect which works via precautionary capital accumulation so as to better prepare when the disaster eventually hits.…”
Section: Introductionmentioning
confidence: 99%